Meanings and practices of the physical activity engaged in by Moroccan women in an Islamic urban environment: A quasi‐ethnography - Lourdes Rubio‐Rico; Inmaculada deMolina‐Fernández; Isabel Font‐Jiménez; Alba Roca‐Biosca (Wiley, 2021)
Abstract Aim To understand the meanings and practices of the physical activity (PA) engaged in by Moroccan women in an Islamic urban environment. Design Quasi‐ethnographical study. Methods 13 semi‐structured interviews and 15 observation sessions of the PA engaged in by women. Results The concept of PA fits into the holistic approach of Islam. The social and cultural conditions of those who regularly practise PA are diverse. The community collaborates to overcome difficulties involved with this practice. The flexibility of issues such as gender segregation and clothing, Islam as a stimulus for PA, health as a value, the promotion of a rights and duty‐based model for health care user, the community co‐creation of the PA offer, and the power of organized civil society could inspire new strategies for the promotion of PA among Muslim women in other contexts.